Association of biochemical markers with time of onset and severity of hypertensive disorder of pregnancy - Jaiswal, Aditi; Hooja, Nupur; Sharma, Pooja; Monika; Verma, Krupa; Panwar, Babita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Hypertensive disorders of pregnancy (HDP) are a common cause of morbidity and mortality. Inflammation is considered as one of the etiologic factors along with a complex interplay of multiple genetic, nutritional and other environmental agents. This study was undertaken to find association of biochemical markers with severity and time of onset of HDP. Methods: Institutional review board and ethics committee approval was taken prior to the study. History and examination was done. Blood pressure was recorded at each antenatal visit. Blood samples were taken for the study of biochemical markers-hsCRP and interleukin 6 levels. Data was analyzed. P value <0.05 was taken as significant. Results: Of the 80 women, 27.5% had early onset HDP. 72.5% had severe HDP. Inflammatory indices were altered as compared to the range of normal pregnant women. Mean IL-6 and hsCRP levels were found to be raised but no statistically significant association was observed between IL-6 levels or hs-CRP levels and time of onset of HDP (p value = 1 and 0.5859 respectively and severity of onset of HDP (p value = 0.197 and 0.453 respectively). Conclusions: Biochemical indices, IL-6 and hs-CRP levels were elevated in women with HDP, indicative of increased inflammation.